2021
DOI: 10.30897/ijegeo.828668
|View full text |Cite
|
Sign up to set email alerts
|

Geological and Geospatial Mapping of Vulnerability Areas for Proper Flood Mitigation: Ganaja, Lokoja Metropolis, North-Central Nigeria

Abstract: This study aimed at the geological and geospatial mapping of flood vulnerable areas in Ganaja, Lokoja metropolis for proper flood mitigation. The geological mapping of the study area involved taking several traverses and understudying the different rock types in the study area. Fractures and joint within the rocks show NW-SE, NNE-SSW orientations; corresponding to the predominant stress direction that represent imprints of the Pan-African Orogeny. Buildings within 100 meters buffer distance from the river bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Flood Susceptibility Assessment mapping is a very important tool needed to hinder the continuous events of the flood, which aids in reducing the adverse effects of flood hazards. Although it is impossible to prevent the occurrence of floods, it is possible to predict these catastrophic events, and to some extent, control those using appropriate methods and analyses (Cloke and Pappenberger, 2009;Farina et al, 2018;Moazzam et al, 2018;Menteş et al, 2019;Ozulu et al, 2021). Also, the necessary measures to prevent floods and mitigate their adverse effects seem inevitable (Huang et al, 2008;Dang et al, 2011;Alvarado-Aguilar et al, 2012), one of which is undoubtedly the development of flood susceptibility maps (Bubeck et al, 2012;Direk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Flood Susceptibility Assessment mapping is a very important tool needed to hinder the continuous events of the flood, which aids in reducing the adverse effects of flood hazards. Although it is impossible to prevent the occurrence of floods, it is possible to predict these catastrophic events, and to some extent, control those using appropriate methods and analyses (Cloke and Pappenberger, 2009;Farina et al, 2018;Moazzam et al, 2018;Menteş et al, 2019;Ozulu et al, 2021). Also, the necessary measures to prevent floods and mitigate their adverse effects seem inevitable (Huang et al, 2008;Dang et al, 2011;Alvarado-Aguilar et al, 2012), one of which is undoubtedly the development of flood susceptibility maps (Bubeck et al, 2012;Direk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to a report by United Nations Office for Disaster Risk Reduction, it was reported that floods account for more than 40% of all the globally recorded disasters which took place between 1998 and 2017 (Nguyen et al, 2023). Although flood occurrence is difficult to prevent, predicting these catastrophic events requires appropriate methods and analysis (Cloke and Pappenberger 2009;Farina et al, 2018;Isiaka et al, 2023;Mentes et al, 2019;Moazzam et al, 2018;Ozulu et al, 2021). The occurrence of floods can result in threats of changes that can influence the temporal and spatial configuration of human life, loss of property, as well as having effects on agriculture and the environment.…”
Section: Introductionmentioning
confidence: 99%